Impact of anthocyanins derived from Dioscorea alata L. on growth performance, carcass characteristics, antioxidant capacity, and immune function of Hainan black goats - Feng, Haibo; Shi, Huiyu; Yang, Fengyuan; Yun, Yanhong; Wang, Xuemei (Frontiers in Veterinary Science, 2023)
The objective of this investigation was to assess the impact of anthocyanins sourced from Dioscorea alata L. on the growth, carcass traits, antioxidant potential, and immune response of Hainan Black Goats. In this study, 30 three-month-old Hainan black goats (with a weight of 11.30 ± 0.82 kg) were selected and randomly divided into two groups, with 15 goats in each group. During the 60-day experiment, the control group (CON) and the treatment group (DAC) were respectively supplemented with 0 and 40 mg/kg BW of DAC in the basal diet. The results showed that DAC had no significant impact on the growth performance and body characteristics of Hainan black goats (p > 0.05). However, in terms of meat quality, the addition of DAC significantly increased the pH value and cooking yield 24 hours post-slaughter (p < 0.05), while reducing the shear force of the meat (p < 0.05). Compared to the control group, adding DAC to the feed resulted in a significant increase in the total antioxidant capacity (T-AOC) and superoxide dismutase (T-SOD) concentrations in plasma after 30 days of feeding (p < 0.05). After 60 days of feeding, the concentrations of T-AOC, T-SOD, glutathione peroxidase (GSH-Px), and catalase (CAT) in the plasma of the DAC group was higher than that of the control group (p < 0.05), while the concentration of malondialdehyde (MDA) was lower than that of the control group (p < 0.05). In addition, supplementing DAC significantly increased the content of interleukin-10 (IL-10) and immunoglobulin M (IgM) in the plasma of Hainan black goats after 30 days of feeding (p < 0.05), while reducing the content of interleukin-6 (IL-6) (p < 0.05). After 60 days of feeding, the immunoglobulin G (IgG) and IL-10 content in the plasma of the DAC group was significantly increased (p < 0.05), while the concentrations of IL-1β, IL-6, and tumor necrosis factor-α (TNF-α) were suppressed (p < 0.05). In summary, these results indicate that supplementing DAC can improve the meat quality, enhance the antioxidant capacity, and immune function of Hainan black goats.